IMPLEMENTASI KEBIJAKAN MEMENUHI KETERWAKILAN PEREMPUAN PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2019 DI KABUPATEN BIAK NUMFOR - Evelin Agustina Marani; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2022)
The purpose of this study is to describe and find out the implementation of policies to fulfill women's representation in the 2019 legislative general election in Biak Numfor Regency and also to find out the level of supporters and obstacles in fulfilling women's representation in Biak Regency. The type of research used in this study is descriptive qualitative. Data collection techniques used in collecting research data are in-depth interviews, observation, and document studies. The results of the research on Policy Implementation meet the representation of women in the Biak Numfor district. The implementation of the policy on the placement or implementation of women's representation in the general election of the legislature requires the need for gender justice in party management and implementing a 30% quota policy for women's representation in the list of legislative candidates. Power interests and strategies involved in policy implementation. It is also necessary to take into account the strengths of the actors involved to facilitate a policy. Inhibiting and supporting factors in implementing policies to fulfill women's representation are more on structural, institutional, and cultural constraints that must be more organized so that they can provide sufficient space for an applicable regulatory requirement so that it can meet the requirements in implementation. election